The Role of Apoptosis in Acetaminophen Hepatotoxicity - Jaeschke, Hartmut (Food Chem Toxicol, 2018)
Although necrosis is recognized as the main mode of cell death induced by acetaminophen (APAP) overdose in animals and humans, more recently an increasing number of publications, especially in the herbal medicine and dietary supplement field, claim an important contribution of apoptotic cell death in the pathophysiology. However, most of these conclusions are based on parameters that are not specific for apoptosis. Therefore, the objective of this review was to re-visit the key signaling events of receptor-mediated apoptosis and APAP-induced programmed necrosis and critically analyze the parameters that are being used as evidence for apoptotic cell death. Both qualitative and quantitative comparisons of parameters such as Bax, Bcl-2, caspase processing and DNA fragmentation in both modes of cell death clearly show fundamental differences between apoptosis and cell death induced by APAP. These observations together with the lack of efficacy of pan-caspase inhibitors in the APAP model strongly supports the conclusion that APAP hepatotoxicity is dominated by necrosis or programmed necrosis and does not involve relevant apoptosis. In order not to create a new controversy, it is important to understand how to use these “apoptosis” parameters and properly interpret the data. These issues are discussed in this review.